PELATIHAN PENGEMBANGAN MODUL AJAR INOVATIF BAGI GURU SD DI KECAMATAN PENGASIH KABUPATEN KULON PROGO - Ali Mustadi; Setiawan Edi Wibowo; Febrina Siska Widyaningtyas; Sandy Abdi Kusumah (Jurnal Padamu Negeri, 2026)
The independent curriculum requires that each educational unit and teacher is able to develop learning tools in accordance with the characteristics of students and the conditions of each educational unit. However, this program has not been well understood by each educator spread across Indonesia. The lack of understanding of educators is related to how to develop learning tools. Learning tools teaching modules, teaching materials, learning media, LKPD, and assessment instruments become something unfamiliar to entities. Such conditions are also experienced by private elementary schools spread across the Pengasih District, Kulon Progo Regency. The purpose of this community service activity is to describe the improvement of the understanding of educators at SD Pengasih District, Kulon Progo Regency in developing innovative teaching modules. The method of implementing community service activities begins with workshops and socialization, continues with mentoring, implementation, reflection, and follow-up, and ends with the collection of reports and innovative teaching modules based on literacy, local culture, and natural resources for grades 1 to 6 of elementary school. The result of this service is that elementary school teachers in Pengasih District, Kulon Progo Regency have succeeded in creating innovative teaching modules that have been IPR-kan.